Obesity Paradox in Short-Term Clinical Outcomes After Percutaneous Coronary Interventions (Bangladesh Heart Journal, 2021)
Background: The “obesity paradox”, a counterintuitive decrease in morbidity and mortality with increasing body mass index (BMI), has been shown in patients when acute cardiovascular decompensation occurs. However, whether this phenomenon exists in patients undergoing percutaneous coronary intervention (PCI) is not well known. The existence of obesity paradox and its impact on short-term clinical outcomes after PCI have not been thoroughly investigated, especially in Bangladesh.Methods: This cross-sectional observational study was conducted at National Institute of Cardiovascular Diseases, Dhaka, in 100 patients who underwent PCI. They were divided in two groups on the basis of BMI of Asian ethnicity: Group I (BMI < 23 kg/m2) and Group II (BMI